2020
DOI: 10.3390/su12145759
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis between Global University Rankings and Environmental Sustainability of Universities

Abstract: Global University Rankings (GURs) intend to measure the performance of universities worldwide. Other rankings have recently appeared that evaluate the creation of environmental policies in universities, e.g., the Universitas Indonesia (UI) GreenMetric. This work aims to analyze the interaction between the Top 500 of such rankings by considering the geographical location of universities and their typologies. A descriptive analysis and a statistical logistical regression analysis were carried out. The former dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…Evaluating and surveying HEIs' quality and reputation are highly useful as well to know their opinions concerning the weighting to assign to indicators for international comparative evaluations. Similar studies with this finding include (Astin & Solmon, 2012;Fayolle & Redford, 2014;Han & Xu, 2019;Jöns & Hoyler, 2013;Khamala, Makori, & Njiraine, 2018;Mukhwana et al, 2016;Muñoz-Suárez et al, 2020).…”
Section: Ranking Discrepancies and Resemblancessupporting
confidence: 63%
“…Evaluating and surveying HEIs' quality and reputation are highly useful as well to know their opinions concerning the weighting to assign to indicators for international comparative evaluations. Similar studies with this finding include (Astin & Solmon, 2012;Fayolle & Redford, 2014;Han & Xu, 2019;Jöns & Hoyler, 2013;Khamala, Makori, & Njiraine, 2018;Mukhwana et al, 2016;Muñoz-Suárez et al, 2020).…”
Section: Ranking Discrepancies and Resemblancessupporting
confidence: 63%
“…As far as we know, this is the first empirical research work to merge a university global indicator such as THE with a sustainability indicator of HEIs based on their SDG progress to measure the extent to which the SDGs are related to the best universities' overall rankings. To date, the aim of university rankings has only been to evaluate universities' academic and research reputation or their performance for promotion purposes [71,72], which does not necessarily mean that HEIs make any societal contribution [73][74][75]. In fact, as part of the metric management model included in the higher education system worldwide, university leaders have carefully paid attention to the quantitative metrics considered by international rankings (QS World Ranking, Shanghai Ranking, The World University Ranking, Scimago Institutions Ranking), such as the citation indicators in research evaluation and funding [73][74][75][76], whereas other qualitative dimensions, e.g., HEIs' societal contribution, have been neglected.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the aim of university rankings has only been to evaluate universities' academic and research reputation or their performance for promotion purposes [71,72], which does not necessarily mean that HEIs make any societal contribution [73][74][75]. In fact, as part of the metric management model included in the higher education system worldwide, university leaders have carefully paid attention to the quantitative metrics considered by international rankings (QS World Ranking, Shanghai Ranking, The World University Ranking, Scimago Institutions Ranking), such as the citation indicators in research evaluation and funding [73][74][75][76], whereas other qualitative dimensions, e.g., HEIs' societal contribution, have been neglected. If this were true, then HEIs' leaders would be responsible for promoting elitism instead of equity and diversity through performance-based incentives [50,[76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…They considered to fulfill the sustainable knowledge to their curriculums (94.1%), support the educational system to embed the sustainable awareness to staff and students (82.4%), and supported the researchers to discover new innovations related to sustainability in their research (41.2%), whereas Group 2 had less educational system and research that support the sustainability (5.3%). Therefore, it can be concluded that the sustainable education performance can be enhanced by a green university ranking because it encourages academics based on sustainability, which is the basic objective of a green ranking [50][51][52][53].…”
Section: Contribution Of Ui-greenmetric To Hei's Sustainability Activitiesmentioning
confidence: 99%